Role of adipose tissue-derived stem cells in the progression of renal disease - Cassiano Donizetti-Oliveira; Patricia Semedo; Marina Burgos-Silva; Marco Antonio Cenedeze; Denise Maria Avancini Costa Malheiros; Marlene Antônia dos Reis; Alvaro Pacheco-Silva; Niels Olsen Saraiva Câmara (Einstein (São Paulo), 2011)
ABSTRACT Objective: To analyze the role of adipose tissue-derived stem cells in reducing the progression of renal fibrosis. Methods: adipose tissue-derived stem cells were isolated from C57Bl/6 mice and characterized by cytometry and differentiation. Renal fibrosis was established after unilateral clamping of the renal pedicle for 1 hour. Four hours after reperfusion, 2.105 adipose tissue-derived stem cells were administered intraperitoneally and the animals were followed for 24 hours during 6 weeks. In another experimental group, 2.105 adipose tissue-derived stem cells were administered only after 6 weeks of reperfusion, and they were euthanized and studied 4 weeks later. Twenty-four hours after reperfusion, the animals treated with adipose tissue-derived stem cells displayed reduced renal and tubular dysfunction and an increase of the regenerative process. Renal expression of IL-6 and TNF mRNA were decreased in the animals treated with adipose tissue-derived stem cells, while the levels of IL-4, IL-10, and HO-1 were increased, despite the fact that adipose tissue-derived stem cells were not observed in the kidneys via SRY analysis. Results: In 6 weeks, the kidneys of non-treated animals decreased in size, and the kidneys of the animals treated with adipose tissue-derived stem cells remained at normal size and display less deposition of type 1 collagen and FSP-1. The renal protection observed in animals treated with adipose tissue-derived stem cells was followed by a drop in serum levels of TNF-α, KC, RANTES, and IL-1a. Treatment with adipose tissue-derived stem cells after 6 weeks, when the animals already displayed established fibrosis, demonstrated an improvement in functional parameters and less fibrosis analyzed by Picrosirius stain, as well as a reduction of the expression of type 1 collagen and vimentin mRNA. Conclusion: Treatment with adipose tissue-derived stem cells may deter the progression of renal fibrosis by modulation of the early inflammatory response, likely via reduction of the epithelial-mesenchymal transition.